Dormand-Prince Method for Solving SIR Model for Hand, Foot and Mouth Disease in Sarawak - Musa, Aideena Umairah; MD SUDIN, AZILA (Enhanced Knowledge in Sciences and Technology, 2026)
Mathematical modelling is essential in understanding the transmission of Hand, Foot and Mouth Disease (HFMD), which is remains considerable public health issue, especially among children. The aims of this study to understand the transmission dynamics of HFMD in Sarawak using the Susceptible-Infected-Recovered (SIR) model as its numerical approach. This study focuses on solving the system of ordinary differential equations controlling the SIR model using the Dormand-Prince method (RK45). MATLAB was utilized to perform numerical simulations of the SIR model using real epidemiological data. Three different step size h = 0.1,0.05 and 0.01 used to see the effect of step size to the numerical obtain when RK45 applied. The numerical result show that the RK45 produces stable and consistent solutions. The RK45 also successfully demonstrate the transmission dynamics of HFMD. In conclusion, the results prove that the RK45 is an effective numerical approach for solving the SIR model of HFMD in Sarawak.